#### Answer

$y - 3 = \frac{4}{3}(x - 1)$

#### Work Step by Step

The first thing we want to do in this problem is figure out two points on this graph. Once we have these two points, we can find the slope.
We can see that the graph passes through the point $(1, 3)$ and the point $(-2, -1)$.
Let's use the formula to find the slope $m$ given two points:
$m = \frac{y_2 - y_1}{x_2 - x_1}$
Let's plug in the values into this formula:
$m = \frac{-1 - 3}{-2 - 1}$
Subtract the numerator and denominator to simplify:
$m = \frac{-4}{-3}$
Divide the numerator and denominator by $-1$:
$m = \frac{4}{3}$
Now that we have the slope, we can use one of the points and plug these values into the point-slope equation, which is given by the formula:
$y - y_1 = m(x - x_1)$
Let's plug in the points and slope into the formula:
$y - 3 = \frac{4}{3}(x - 1)$